Non-Alcoholic Fatty Liver Disease Research 2016 - Amedeo Lonardo (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This new book entitled "Non-Alcoholic Fatty Liver Disease Research 2016" covers a selection of recent research topics and current review articles in the field of nonalcoholic fatty liver disease (NAFLD) that have been recently published in a monographic Special Issue of the International Journal of Molecular Sciences (IJMS) journal. NAFLD is an "umbrella" definition that encompasses a spectrum of histopathological liver changes ranging from simple steatosis to nonalcoholic steatohepatitis (NASH) with/without fibrosis, "cryptogenic" cirrhosis and hepatocellular carcinoma. NAFLD has become one of the most common forms of chronic liver disease worldwide and its prevalence is expected to continue rising. It is now becoming increasingly clear that the clinical and economic burden of NAFLD does not only affect the liver, but also affects the risk of developing cardiovascular disease, type 2 diabetes mellitus, colo-rectal neoplasms, chronic kidney disease and other extra-hepatic diseases that have a considerable impact on health-care expenditures. Against this background, further research is needed to better understand the natural history, and the molecular pathogenesis of NAFLD, as well as to elucidate the underlying mechanisms by which NAFLD contributes to the increased cardiometabolic risk, and to disclose novel and effective treatment strategies for this increasingly prevalent and burdensome disease. Some of the leading international researchers in this area expressed a willingness to contribute to this book providing an updated, state-of-the-art view on the aforementioned topics, and also suggesting novel research avenues for NAFLD.